Multi‐attribute node importance evaluation method based on Gini‐coefficient in complex power grids. Issue 9 (1st June 2016) - Wenli, Fan; Ping, Hu; Zhigang, Liu
Abstract : Node importance evaluation contributes to the targeted protection of important nodes, which can enhance the invulnerability of complex power grids against cascading failures. Since the evaluation simply from the perspective of pure topology statistics fails to capture the electrical characteristics of power systems, the authors propose a multi‐attribute node importance evaluation method based on Gini‐coefficient in this study. This method considers not only the electrical characteristics of power grids when evaluation indices are built, but also the impact of the index weight method on the evaluation results. The simulations on the IEEE‐39 system and the 500 kV Center China power system show that the proposed method is suitable to evaluate the node importance in power transmission grids, and can also improve the accuracy of the node importance evaluation.